EXPLORING CLASSROOM INTERACTION PATTERNS IN EFL VIRTUAL LEARNING - Magdahalena Tjalla; Marlina Syamsir; Zulfah Zulfah; Abdul Haris Sunubi; Arqam Arqam (English Review: Journal of English Education, 2023)
Abstract: This study analyzed classroom interaction patterns in four EFL virtual learning classes at IAIN Parepare: speaking, listening, writing, and reading. The purpose of this study was to give an overview of classroom interaction involving lecturers and students during the learning process. The researchers used a video recorder and field notes to capture the spoken and written interaction during the learning process. Data were transcribed and codified based on the intuitive taxonomy of the discourse act framework of Tsui. Data showed that both in spoken and written interaction, patterns of Initiation-Response (IR), Initiation-Response-Follow up (IRF), and Initiation-Response-Follow Up-Follow Up 2 (IRFF) occurred. In detail, the complete interaction patterns were in listening class, both in spoken and written form. In reading and writing classes, the Initiation-Response (IR) and the Initiation-Response-Feedback (IRF) occurred. However, in speaking, only Initiation-Response (IR) was produced. In written interaction, except in the listening class, only Initiation-Response (IR) occurred. Data also showed that utterance categories occurred less in written interaction than in spoken. Most of the interactions were done when the lecturer provided information on learning material and instructions on how to do assignments. Thus, there was no feedback given by the lecturer in this interaction. The study also found that the interaction was lecturer-centered, and both the lecturers and the students employed the L1 in the classroom interaction.